The performance of a lateral flow SARS-CoV-2 antibody assay and semi-autonomous SARS-CoV-2 antisense and sense RNA fluorescence in situ hybridization assay in a prospective cohort pilot study within a Dutch military population. - Inge D Wijnberg; Anton J Soons; Johan G Reimerink; Marit Wiersma; Marie Christine J Plat; Tom van Gool; Gijsbert J Jansen; Cornelis Stijnis; Jack G Koning; Adam Meijer (PLoS ONE)
At the beginning of the COVID-19 pandemic, diagnostic testing was not accessible for mildly ill or asymptomatic individuals. Military operational circumstances exclude the usage of reference laboratory tests. For that reason, at the beginning of the pandemic alternative test methods were needed in order to gain insight into the SARS-CoV-2 status of military personnel. The objectives of this study are to assess whether SARS-CoV-2 antibody rapid lateral flow assay (LFA) in combination with semi-autonomous SARS-CoV-2 antisense and sense genomic RNA fluorescence in situ hybridization (FISH) could establish disease status in military personnel in a fieldable setting, and to assess how this combination performed and to determine which type of sample performed best. A proof of concept sub-study regarding the SARS-CoV-2 application of the fieldable Biotrack-MED® FISH analyzer, a semi-autonomous multi-sample filter cytometer, preceded this observational prospective cohort pilot study. Dutch military personnel were included in the 26 June 2020-11 May 2021 period. Blood, nasopharyngeal and oropharyngeal swabs and saliva were tested at days 0 and 14. SPSS version 25 descriptive statistics and Cohen's kappa assessed agreement between test methods. Both the sensitivity and specificity of the field tests were calculated with ELISA and PCR as reference. Saliva appeared to be the preferred sample type for FISH, where blood was not useful. FISH analysis and LFA results had a concordance of 42% for testing negative, 30% for recovered from infection, 22% for ongoing-and 58% for acute infection in a reference laboratory lab result outcome (RT-PCR or ELISA respectively). The LFA results on serum and full blood corresponded with the ELISA-obtained results (kappa of 0.61 and 0.63 respectively at day 0 and 0.81 and 0.77 respectively at day 14). LFA (full blood-serum), FISH and RT-PCR on saliva did not reach the 90% sensitivity level advised by WHO, with 64-54, 38 and 71% at day 0 and 80-79, 53 and 24% at day 14 respectively.